2012
DOI: 10.5194/acp-12-12255-2012
|View full text |Cite
|
Sign up to set email alerts
|

Modeling uncertainties for tropospheric nitrogen dioxide columns affecting satellite-based inverse modeling of nitrogen oxides emissions

Abstract: Errors in chemical transport models (CTMs) interpreting the relation between space-retrieved tropospheric column densities of nitrogen dioxide (NO<sub>2</sub>) and emissions of nitrogen oxides (NO<sub>x</sub>) have important consequences on the inverse modeling. They are however difficult to quantify due to lack of adequate in situ measurements, particularly over China and other developing countries. This study proposes an alternate approach for model evaluation over East China, by anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 76 publications
4
110
0
Order By: Relevance
“…GEOS-Chem concentrations of NO 2 and H 2 O 2 (proxy for HO 2 ) have been evaluated successfully in a number of aircraft campaigns (Martin et al, 2006;Hudman et al, 2007;Singh et al, 2007;Lin and McElroy, 2010;Mao et al, 2010;Travis et al, 2016). GEOS-Chem NO 2 columns have also been evaluated against satellite observations over China (Lin et al, 2012), North America (e.g., Lamsal et al, 2014), and Africa (Marais et al, 2012). Fast Hg 0 oxidation in the polar spring boundary layer is simulated by specifying high BrO concentrations when conditions for temperature, sea ice cover, sunlight, and atmospheric stability are met .…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
“…GEOS-Chem concentrations of NO 2 and H 2 O 2 (proxy for HO 2 ) have been evaluated successfully in a number of aircraft campaigns (Martin et al, 2006;Hudman et al, 2007;Singh et al, 2007;Lin and McElroy, 2010;Mao et al, 2010;Travis et al, 2016). GEOS-Chem NO 2 columns have also been evaluated against satellite observations over China (Lin et al, 2012), North America (e.g., Lamsal et al, 2014), and Africa (Marais et al, 2012). Fast Hg 0 oxidation in the polar spring boundary layer is simulated by specifying high BrO concentrations when conditions for temperature, sea ice cover, sunlight, and atmospheric stability are met .…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
“…Lin et al (2012) and Stavrakou et al (2013) suggested that the uptake of HO 2 on aerosols is the most important factor but remains largely uncertain. CHASER includes simplified NO x -VOC chemistry related to PANs and isoprene nitrates (Sudo et al, 2002).…”
Section: Other Model Error Sourcesmentioning
confidence: 99%
“…Representations of meteorological parameters, such as cloud optical depth, temperature, water vapor, PBL height, and relevant transport and chemical processes, are also important in tropospheric NO 2 simulations (Lin et al, 2012). Because we employed an AGCM-CTM online coupling system, meteorological fields are simulated explicitly at each model resolution.…”
Section: Other Model Error Sourcesmentioning
confidence: 99%
“…Based on J.-T. Lin et al (2012), we have modified the chemical mechanism as follows. The reaction constants for OH + NO 2 follow Mollner et al (2010) for low-and high-pressure limits, i.e., k 0 = 1.48 × 10 −30 × (T /300) −3 cm 6 molecule −2 s −1 , and k inf = 2.58 × 10 −11 cm 3 molecule −1 s −1 .…”
Section: Two-way Coupled Geos-chem Model Systemmentioning
confidence: 99%
“…Many of these models tend to overestimate the tropospheric ozone in the Northern Hemisphere Stevenson et al, 2006;Fiore et al, 2009;Reidmiller et al, 2009;Young et al, 2013;Parrish et al, 2014). Previous studies have suggested various sources of model biases in emissions, chemical mechanisms, meteorological inputs and model resolutions Lin et al, 2008;Weaver et al, 2009; J.-T. Lin et al, 2012;Doherty et al, 2013;Parrish et al, 2014;Fiore et al, 2014;Fu et al, 2015;Monks et al, 2015). Lack of capability in representing small-scale processes not resolved by the coarse-resolution global models may be an important factor for model biases, whereas the quantitative effect is much less clear, especially for the global effect of processes at scales below 100 km.…”
Section: Introductionmentioning
confidence: 99%